Edukasi pencegahan dan penanganan injury akibat kecelakaan lalu lintas pada masyarakat Kab Way Kanan - Aulia Fitri Rahmasari; Silvia Prestiawanti; Febrima yuniar; Isnaini Nurul Hikmah; Dani Martalaga; Sulistiowati .; Bunga lana Rajuna; fresilia damayanti; Andine Tika Puspita; Dani Prasetyo; Ryan Aditya; Rabiul Anwar; jumhuriah Handayani; Rieskan esa Fani; Kus Apri Wibowo; Hendriansyah Hendriansyah; Nizar Alzamna; Alandra Tyas Ananda; Alya Regina Natasya; Tandok Andani; Haris Hastiar (FKM UIN Sumatera Utara Medan, 2025)
Traffic accidents are one of the leading causes of injury and death in Indonesia. Lack of public knowledge about first aid and injury prevention contributes to the high rate of morbidity and mortality. This community service activity aimed to increase public understanding and awareness regarding the prevention and management of injuries caused by traffic accidents. The activity was carried out through an educational and training approach using lectures, discussions, and demonstrations by nursing students specializing in emergency care from Universitas Aisyah Pringsewu. The participants consisted of community members living around the service area who were actively involved in the sessions. The materials included basic concepts of injury prevention, safe driving behavior, and first aid techniques for victims of road traffic accidents. The results showed that participants demonstrated improved knowledge and skills in handling injuries and increased awareness of traffic safety. Evaluation was conducted through pre- and post-tests, as well as direct observation during practice. This community service program succeeded in enhancing public competence in providing first response to traffic injuries and fostering a culture of safety on the road. In conclusion, educational activities regarding injury prevention and management can effectively improve community readiness in responding to emergency situations resulting from traffic accidents.